Historical Memory in the Context of U.S. Foreign Policy: The Case of the Presidency of Joseph Biden - L. M. Sokolshchik; E. Z. Galimullin; A. V. Bondarenko; V. M. Semenov (Международная аналитика)
Modern day politicians often refer to historical memory in order to construct and/or adjust foreign policy. The analysis of historical memory as one of the tools for constructing foreign policy narratives is attracting increasing scientific interest in the study of international relations. Under conditions of deep socio-political split in the USA and fragmentation of American identity, representatives of the Democratic administration actively turn to historical memory, trying to explain the changing international realities and justify the implemented foreign policy course. The article attempts to identify the key historical narratives of the Biden Administration and analyze how their use influences the foreign policy of the U.S. at the present stage. To achieve this goal, the authors used the method of narrative interpretation to conduct a qualitative analysis of a broad source base (speeches, interviews, press conferences of key representatives of the U.S. executive branch). As a result, a number of foreign policy narratives with the most characteristic historical subjects for the current administration were identified. It has been established that U.S. leaders address historical memory as part of discourses on the promotion of liberal democracy in the world; the limits of “hard power” and the fight against international terrorism; human rights and freedoms; relations with Russia; and the defense of a liberal world order. It is determined that historical narratives are often used by the United States to legitimize its unilateral and discriminatory foreign policy actions. The authors conclude that for the current administration the construction of foreign policy narratives through selective reference to the subjects of American historical memory becomes one of the key tools of adaptation to the development of international multipolarity, mobilization of its resources and consolidation of allies to defend the “free world” from “illiberal” opponents.